The big bang theory. The complete fourth season [videorecording (DVD)] - Parsons, Jim, 1973-; Galecki, Johnny; Cuoco, Kaley; Helberg, Simon; Nayyar, Kunal (Warner Bros. Entertainment : Distributed by Warner Home Video, 2011)
This season the Big Bang gang's romantic universe expands. On the rebound from Penny, Leonard falls into the arms of Raj's sister Priya. Sheldon gets a girlfriend, or rather a friend who is a girl: Amy, a dour neurobiologist who declares herself besties with Penny. Howard and Bernadette heat up. And so do Raj and Bernadette (at least in Raj's Bollywood daydream). All in the furtherance of award-winning genius comedy.